DETERMINING OF NEUTRAL AND UNSTABLEWIND PROFILES OVER BAGHDAD CITY - Al-Jiboori, Monim (Iraqi Journal of Science, 2024)
This paper provides a comprehensive analysis of slow-response observationstaken over the centre of Baghdad city (Bab Al-Mhadham area). Measurements weretaken at two levels: 15 and 20 m and then wind speed profiles were derivedaccording to atmospheric stability indicated by Richardson number in the lower partof planetary boundary layer. These profiles were constructed by logarithmic andpower-exponent laws after checking estimated winds at the same heights by theselaws with those observed. The estimated values of wind at these levels were in goodagreement with observed values. Mean wind profiles calculated from both laws havelogarithmic behavior especially in neutral conditions. They have the same shape andvalues at lower heights up to 50 m and then gradually deviate from each other overthis height. Lastly, drag coefficient at each level was calculated and then its resultsfound to be constant over neutral regime and increased with increasing instability.